Evaluation of the human amniotic membrane as a scaffold for periodontal ligament fibroblast attachment and proliferation - Elahi, Asrar; Haslina Taib,; Zurairah Berahim,; Azlina Ahmad,; Suzina Sheikh Ab Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study was aimed at evaluating the ability of the human amniotic membrane (HAM) to act as a scaffold for the growth of the main cells in periodontal regeneration, human periodontal ligament fibroblasts (HPDLFs). The HAM has many biological properties that are suitable for periodontal tissue regeneration such as low immunogenicity, anti-fibrosis, anti-inflammation, and a rich extracellular matrix component. Commercially available HPDLFs were seeded onto the HAM, and the attachment and proliferation of the cells were observed through scanning electron microscopy (SEM) and histological analysis. Cell viability was assessed using the alamarBlue® proliferation assay at days 1, 3, 7, 14 and 21. Histologically, the HPDLFs showed a monolayer to multilayer attachment onto the HAM from day 1 to day 7. The SEM analysis demonstrated that the HPDLFs had attached appropriately onto the HAM surface at day 1 to day 3, and began overlapping at day 7, while maintaining their flat shape. However, by days 14 and 21, there was an alteration in the morphology of the cells, where they later became rounded. The proliferation assay showed that the viability of the HPDLFs on the HAM had increased significantly from day 1 to day 7 (p=0.012), but later showed significant reduction at day 14 (p=0.002) and day 21 (p=0.005). In conclusion, this study showed that the HAM was able to function well as a scaffold for HPDLFs within 7 days, and thus, it can be a promising scaffold for periodontal regeneration. However, the behaviour of the cells in relation to the membrane over longer culture duration warrants further investigation.